Petro Elastic Modeling for enhancement of hydrocarbon prediction: Case study in SE Asia - Babasafari, A.A. (2019)
One of the widely used methods for litho-facies classification in oil and gas fields is conducted through cross plotting elastic properties e.g. Acoustic Impedance vs. Vp/Vs ratio. First at well locations the cross plot is color coded by litho-facies classes. Afterwards, to predict litho-facies away from the wells, pre-stack seismic data inversion is performed. Cross plot of predicted elastic properties between the wells aid to discriminate each class. However, discrimination of defined litho-facies classes represents uncertainty particularly at overlapped zones between classes. This study reveals how Petro Elastic Modeling (PEM) generates a more suitable differentiation of litho-facies classification through elastic properties estimation. This process allows predicting the hydrocarbon zones more precisely and rational continuity of pay-zone layers is obtained due to high confidence value of each class in Bayesian probability classification. Â© 2018 SEG.